The life and works of Geronima T. Pecson - Tarlit, Rodolfo Y. (Institute of Library Science, University of the Philippines Diliman, 1985)
This is a historical and bibliographical study which presents a narrative record of the life history and works of Geronima T. Pecson from the time of her birth to the present. It identifies, describes and evaluates her achievements and contributions to education, social work, health, community and rural improvements, politics and international affairs; and compiles a bibliography of her various works - books, articles, book reviews, speeches, messages, statements, interviews and reports - both published and unpublished from 1929 to 1980.